How to combine the hipolipemic drugs? - Kłosiewicz-Latoszek, Longina; Cybulska, Barbara (Przewodnik Lekarza/Guide for GPs, 2005)
Statins and fibrates are the most frequently used medicines in clinical practice. Statins are pharmaceuticals of choice in subjects with elevated concentrations of LDL-cholesterol. Fibrates are useful mainly in persons with low concentrations of HDL-cholesterol and/or high ceoncentrations of triglycerides. In patients with severe hypertriglyceridemia or with mixed hiperlipidemia or aterogenic dyslipidemia optimal target effects achieved with one drug are not always as good as expected or such therapy leads to adverse symptoms, when maximal doses are applied. Theoretically all hipolipemic drugs could be combined each with other, especially when different effects on mechanisms of lipids metabolism are considered. Combination of statins and fibrates is the most frequently used and reasonable in clinical practice. Combination of statins and nicotic acid is also favorable, but rarely used because of side effects observed after nicotic acid. Combinations of statins with new hipolipemic agents (ezatimib, CEPT inhibitors) have been tested in clinical trials. Combined hipolipemic drugs therapy allow to achieve higher percentage of lipids’ concentration changes as well as higher percentage of subjects achieve targets of the therapy than after monotherapy. This type of therapy could be considered in subjects with high cardiovascular disease risk accompanied with severe lipids disturbances.